(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
Bank credit is extremely important, as the generated revenues by a main focus of any bank earnings no matter how many and varied sources of revenue other, and without losing the bank and the main role function as an intermediary in financial economics . But at the faltering customers in payment of loans . Therefore , uses a method of financial analysis using ratios as one of the important tools to measure the clients ability to pay , in spite of the need for the Bank analyzed the trend in this regard is focused on three main areas ( liquidity, profitability, and borrowing ) and can be to add another field is the possibility to cover fixed charges of the profits generated. Finally I would like to emphasize the importance of relying on financial analysis in judging the size of the risks involved in the drive. It is this analysis reveal a prior censorship for the safety of the financial position of the client before getting involved with him in any guarantees provided by the customer of the bank. Providing mortgage loan may not return for a complete coverage of the risks, and that if they went bankrupt enterprise and the failure of the bank in the sale of the mortgaged asset worth enough to repay the loan amount and interest. Add to Phrasebook No word lists for English -> Arabic... Create a new word list... Copy